Effect of multi-wall carbon nanotubes/strontium ferrite nanoparticles on the microstructure, phase, magnetic and electromagnetic behavior of carbon aerogel composites - Mehdi Mazaheri Forushani; Gholamreza Gordani; Ali Ghasemi; Mohammad Reza Loghman Estarki; Shahab Torkian; Hossein Jamali; Majid Tavoosi; Esmail Kiani (Journal of Materials Research and Technology, 2023)
This research examined the electromagnetic behavior of a carbon aerogel composite containing multi-wall carbon nanotubes and strontium ferrite nanoparticles within the X band range (8.12–2.4 GHz). For this purpose, 10 wt% of carbon nanotubes and 5 wt%, 10 wt%, and 15 wt% of strontium ferrite nanoparticles were applied in the pyrolyzed cellulose aerogel composite. For structural and magnetic characterization of the samples, different techniques such as X-ray diffraction test, Fourier transform infrared spectroscopy, field emission scanning electron microscopy, vector network analyzer, and vibrational magnetometer (VSM) were used. The VSM results indicated that the presence of 10 wt% strontium ferrite nanoparticles in the carbon aerogel substrate caused saturation magnetization of 2.31 emu/g. However, upon adding 10 wt% carbon nanotubes, the saturation magnetization value reached 6.82 emu/g. Based on the results, the greatest shielding efficiency (within the X-band = 110 ± 0.8 dB) occurred in the sample containing 10 wt% carbon nanotube alongside 5 wt% strontium ferrite at thicknesses of 4 mm. Furthermore, the reflection loss value of this sample was −48.59 ± 0.5 dB at a thickness of 3 cm and a frequency of 10.92 GHz.